A sustained deviance response evoked by the auditory oddball paradigm - Kretzschmar, Britta; Gutschalk, Alexander (Clinical neurophysiology, 2010)
Objective - Previous studies have suggested that the MMNm is related to selective adaptation of the N1m. Since selective adaptation has also been reported for the sustained field, we hypothesized a second deviance response in addition to the MMNm. The present study evaluated the existence of this wave. - Methods - Magnetoencephalography was used to record deviance responses for pure tones of 1000 and 1050Hz. Tone duration was 50, 150, or 600ms in separate sets. Our hypothesis was that a sustained deviance response would increase with tone duration. - Results - The data revealed a sustained deviance response with a similar source configuration as the main MMNm, but a distinct time course. The sustained deviance response increased with the tone duration, but less than the standard sustained field. Moreover, the sustained deviance response was already present for short (50ms) tones. - Conclusions - The MMNm is followed by a sustained deviance response in the oddball paradigm. While some characteristics of the response coincide with the sustained field, its growth with tone duration differs. The response could possibly be related to automatic orienting of attention, but further studies are required to explore its functional role. - Significance - The sustained deviance response is a separate component - distinct from the MMNm and P3 - that needs to be considered in the evaluation of data obtained with the auditory oddball paradigm.